Attribute-Based Encryption and Access Control - Huang, Dijiang; Dong, Qiuxiang; Zhu, Yan (Professor of computer security) (Boca Raton : CRC Press LLC, 2020)
This book covers a broader scope of Attribute-Based Encryption (ABE), from the background knowledge, to specific constructions, theoretic proofs, and applications. The goal is to provide in-depth knowledge usable for college students and researchers who want to have a comprehensive understanding of ABE schemes and novel ABE-enabled research and applications. The specific focus is to present the development of using new ABE features such as group-based access, ID-based revocation, and attributes management functions such as delegation, federation, and interoperability. These new capabilities can build a new ABE-based Attribute-Based Access Control (ABAC) solution that can incorporate data access policies and control into ciphertext. This book is also ideal for IT companies to provide them with the most recent technologies and research on how to implement data access control models for mobile and data-centric applications, where data access control does not need to rely on a fixed access control infrastructure. It's also of interested to those working in security, to enable them to have the most recent developments in data access control such as ICN and Blockchain technologies. Features Covers cryptographic background knowledge for ABE and ABAC Features various ABE constructions to achieve integrated access control capabilities Offers a comprehensive coverage of ABE-based ABAC Provides ABE applications with real-world examples Advances the ABE research to support new mobile and data-centric applications
3.5.3 Information Theoretical Optimality -- 3.6 System Performance Assessment -- 3.6.1 Communication Overhead -- 3.6.2 Storage Overhead -- 3.6.3 Computation Overhead -- 3.7 Summary -- Chapter 4: Identity Revocable CP-ABE -- 4.1 Introduction -- 4.1.1 Research Contribution -- 4.2 Flexible Group Construction -- 4.3 Why Is the Two-Step ID-Revocable CP-ABE Approach NOT Secure? -- 4.4 Syntax and Security Model -- 4.4.1 Syntax of IR-CP-ABE -- 4.4.2 Security Model -- 4.4.3 Assumptions -- 4.5 Scheme Construction -- 4.5.1 One-ID Revocation for CP-ABE Scheme (OIDR-CP-ABE)
Description based upon print version of record.
4.5.2 Multiple-ID Revocation for CP-ABE Scheme (MIDR-CP-ABE)
OCLC-licensed vendor bibliographic record.
Keywords: Computer networks -- Security measures; Computer security; Identification; Data encryption (Computer science); Computers -- Access control; COMPUTERS / Database Management / Data Mining; COMPUTERS / Security / General; TECHNOLOGY / Engineering / Industrial